2022
DOI: 10.1002/jbt.23283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative cytotoxic assessment of pristine and carboxylic functionalized multiwalled carbon nanotubes on LN18 cells

Abstract: Multiwalled carbon nanotubes (MWCNTs) have been used in biomedical applications due to their ability to enter the cells. Carboxylic functionalization of MWCNT (MWCNT-COOH) is used to mitigate the toxicity of MWCNTs. Our study focuses on comparing the toxicity of MWCNT and MWCNT-COOH on the neuronal cells, LN18. Concentrations of 5, 10, 20, and 40 µg ml −1 were used for the study, and cytotoxicity was determined at 0, 1, 3, 6, 12, 24, and 48 h of incubation. Cell viability was assessed by Trypan Blue, MTT, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Liu et al 18 reported a promising use of CNTs for in vivo cancer treatment in a mouse model. On the other hand, Vijayalakshmi et al 19 have reported that carboxylic functionalized single-walled carbon nanotubes (C-SWCNTs) have increased cytotoxicity effects on human neuronal LN18 cell lines compared to pristine single-walled carbon nanotubes (P-SWCNTs). The increased toxicity of C-SWCNTs was attributed to their oxidized form, which can readily couple to proteins, peptides, or oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 18 reported a promising use of CNTs for in vivo cancer treatment in a mouse model. On the other hand, Vijayalakshmi et al 19 have reported that carboxylic functionalized single-walled carbon nanotubes (C-SWCNTs) have increased cytotoxicity effects on human neuronal LN18 cell lines compared to pristine single-walled carbon nanotubes (P-SWCNTs). The increased toxicity of C-SWCNTs was attributed to their oxidized form, which can readily couple to proteins, peptides, or oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely used nanofiller in order to improve barrier properties are nanoclays, for instant montmorillonite, hectorite and vermiculite, presented the excellent performances when combine with the polymer matrix to obtain nanocomposites, due to the high proportion of filler used and the high‐surface area of the clay particles 12 . However, the carbon‐based materials attracted the attention of the researcher in various sector such as energy and biomedical application specially drug delivery 13–15 . Since the first experimental event of graphene isolation a window was opened with a wide range of research possibility, including the polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, the carbon-based materials attracted the attention of the researcher in various sector such as energy and biomedical application specially drug delivery. [13][14][15] Since the first experimental event of graphene isolation a window was opened with a wide range of research possibility, including the polymer nanocomposites. In the last few decades researchers from different area of expertise, like material, physics, chemistry and engineering have been also trying to use the graphene as filler to improve and control food-packaging properties, including mechanical properties as well as gas barrier.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition to that the major disadvantage of CNTs is their cytotoxicity to the living cells at high concentrations in their native form. 37,38 Therefore CNTs in their native form have limited applications in water purification. Studies have been reported on the use of magnetic nanoparticles supported on CNTs as adsorbents for the removal of MB from water.…”
Section: Introductionmentioning
confidence: 99%
“…One way to make it hydrophilic is the chemical functionalization 36 . In addition to that the major disadvantage of CNTs is their cytotoxicity to the living cells at high concentrations in their native form 37,38 . Therefore CNTs in their native form have limited applications in water purification.…”
Section: Introductionmentioning
confidence: 99%